On the diversification of feedstock in gasification of oil palm fronds - Sulaiman, S.A. (Universiti Malaysia Pahang, 2014)
Co-gasification of biomass can be beneficial since relying on only one type of biomass can interrupt operations if the supply of feedstock is disrupted for any reason. Despite this a gasifier system is usually designed for operation with only one specific feedstock. The gasifying of different biomasses can lead to failure or inefficiency. In this work the gasification of different forms of feedstock derived from oil palm frond was tested in an updraft gasifier that was specially designed for oil palm fronds. The feedstocks considered were dried frond blocks, briquetted fronds and overdried (at 150Â°C) frond blocks. The air flow rate was maintained to the value set for dried fronds in order to investigate the robustness of such configurations. The resulting syngas from the gasification was analyzed in terms of the composition of combustible gases and higher heating value (HHV). Overall, it was found that the altered forms of feedstock caused degradation in the syngas quality, which resulted in a decrease in the HHV of up to 65. Â© Universiti Malaysia Pahang, Malaysia.